New Direction in the Logic of Islamic Law: Through Muhammad Syahrur's Perspective on Qiyas - Muhammad Alim Khoiri (Asy-Syari'ah, 2023)
This research discusses one of Muhammad Syahrur's controversial methodological ideas. Previous studies related to Syahrur mostly analyzed the legal product side rather than the legal excavation methodology. This article aims to find out what Syahrur offers a new concept in Islamic legal methodology, especially in relation to qiyas. Is this offer a purely new methodology or is it actually just a kind of repackaging of a previously existing method? This type of research is library research, that is, examining data related to the discussion by examining the primary book written by M. Syahrur, namely al-KitÄb wa al-Qur'Än QirÄ'ah Mu'Äshirah and several other data . This research resulted in the conclusion that in the update of the ijtihad methodology tools offered by Syahrur, especially in relation to qiyas, there were several theories which had actually been formulated by traditional ushul fiqh scholars, only then Syahrur packaged them in a different wrapper.